Modeling and Analysis of Fasciola Hepatica Disease Transmission - Dagnaw Tantie Yihunie; Joseph Y. T. Mugisha; Dawit Melese Gebru; Haileyesus Tessema Alemneh (Abstract and Applied Analysis)
In this paper, a mathematical model for the transmission dynamics of Fasciola hepatica in cattle and snail populations is formulated and analyzed. The snail mortality rate (μs) is the most important factor that indirectly impacts the basic reproduction number (R0). A 50% change, either an increase or decrease, in the snail mortality rate will result in an approximate 50% change in the opposite direction in the value of R0. The model shows a forward bifurcation at R0=1, indicating that the disease dynamics undergo a critical transition at this threshold. This change signifies a transition from a disease-free state to a persistent infection, highlighting the possibility of a continuous disease presence given specific epidemiological conditions. Simulations show that reducing miracidia, metacercariae, and snail populations, improving treatment, and lowering pathogen transfer between cattle and snails significantly decrease disease prevalence in cattle. To control the disease, transmission rates for cattle and snails must be reduced below γc=1.4338×10−7 and γs=1.1473×10−8, respectively. Current treatments are insufficient, and a combination of improved treatments reduced transmission rates, and increased snail mortality is recommended for better disease control.